Principles of corporate finance law - Eilis Ferran (Oxford University Press, 2008)
This book explores the relationship between law and corporate finance. Corporate finance theory seeks to understand how incorporated firms address the financial constraints that affect their investment decisions by using varied financial instruments that give holders different claims on the firm's assets. Recent scholarship in this area explores precisely how legal mechanisms affect corporate finance and the development of financial markets. The legal environment is crucially important in explaining the choices that companies make about their capital structure